Neurotrophic-tyrosine receptor kinase gene fusion in papillary thyroid cancer : A clinicogenomic biobank and record linkage study from Finland - Zhang, Wei (Impact Journals, 2025)
Selective tropomyosin receptor kinase (TRK) inhibitors are approved targeted therapies for patients with solid tumors harboring a neurotrophic tyrosine receptor kinase (NTRK) gene fusion. Country-specific estimates of NTRK gene fusion frequency, and knowledge on the characteristics of affected patients, are limited. We identified patients with histologically-confirmed papillary thyroid cancer (PTC) from Finland's Auria Biobank. TRK protein expression was determined by pan-TRK immunohistochemistry. Immuno-stained tumor samples were scored by a certified pathologist. Gene fusions and other co-occurring gene alterations were identified by next generation sequencing. Patient characteristics and vital status were determined from linked hospital electronic health records (EHRs). Patients were followed from 1 year before PTC diagnosis until death. 6/389 (1.5%) PTC patients had an NTRK gene fusion (all NTRK3); mean age 43.8 years (and none had comorbidities) at PTC diagnosis. Gene fusion partners were EML4 (n = 3), ETV6 (n = 2), and RBPMS (n = 1). Of 3/6 patients with complete EHRs, all received radioactive iodine ablation only and were alive at end of follow-up (median observation, 9.12 years). In conclusion, NTRK gene fusion is infrequent in patients with PTC. Linkage of biobank samples to EHRs is feasible in describing the characteristics and outcomes of patients with PTC and potentially other cancer types.